2019
DOI: 10.3389/fncel.2019.00391
|View full text |Cite
|
Sign up to set email alerts
|

The WWOX Gene Influences Cellular Pathways in the Neuronal Differentiation of Human Neural Progenitor Cells

Abstract: The brain is the most functionally organized structure of all organs. It manages behavior, perception and higher cognitive functions. The WWOX gene is non-classical tumor suppressor gene, which has been shown to have an impact on proliferation, apoptosis and migration processes. Moreover, genetic aberrations in WWOX induce severe neuropathological phenotypes in humans and rodents. The aim of the present study was to investigate in detail the impact of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Neuronal cell apoptosis was observed in the brain tissues of Wwox −/− mice (Additional file 1: Figure S9). Together, in agreement with a recent study using a human neural progenitor cell culture system [34], our results indicate that loss of Wwox causes disorders in neuronal migration and development and brain malformations in mice.…”
Section: Wwox Is Required For Proper Neuronal Migration and Developmentsupporting
confidence: 92%
See 1 more Smart Citation
“…Neuronal cell apoptosis was observed in the brain tissues of Wwox −/− mice (Additional file 1: Figure S9). Together, in agreement with a recent study using a human neural progenitor cell culture system [34], our results indicate that loss of Wwox causes disorders in neuronal migration and development and brain malformations in mice.…”
Section: Wwox Is Required For Proper Neuronal Migration and Developmentsupporting
confidence: 92%
“…WWOX has been shown to be highly expressed in the secretory epithelial cells of hormonally regulated organs including breast, ovary, testis and prostate, and targeted deletion of Wwox in mouse mammary gland leads to impaired mammary ductal development [1,53]. WWOX expression is relatively strong in human, rat and mouse neural tissues, and varies according to the location [19,34,53,61]. Notably, WWOX may interact with steroid hormone 17β-estradiol via its NSYK (Asn-Ser-Tyr-Lys) motif in the C-terminal short-chain alcohol dehydrogenase/reductase domain for neuroprotection [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cerebral cortex PAS-stain revealed irregular migration trajectories of glial cells, known to be important in the guidance of migrating neurons. Interestingly, it has been previously showed by some of us (KK, AKB) that Wwox silencing in neural progenitor cells may alter the expression of a large number of genes (e.g., DCLK, NEFM, and NEFL) involved in neurofilament assembly, cytoskeleton organization and chromatin remodeling (Kośla et al, 2019). In the present study, we performed detailed analysis of gene expression of Wwox-depleted neural progenitors and differentiated post-mitotic neurons.…”
Section: Discussionmentioning
confidence: 81%
“…To analyze the transcriptomic changes caused by WWOX depletion in human neuronal progenitor cells (hNPC), and their putative connection to observed disease phenotypes, we employed the data (deposited in GEO Database with accession number GSE126075), obtained in the experiment of in vitro WWOX silencing in H9-derived hNPC as previously described by some of us (Kośla et al, 2019). WWOX was silenced by a shRNA lentiviral delivery system and the transcriptome was analyzed by CAGE (cap analysis of gene expression) method.…”
Section: Transcriptomic Analyses Of Hnpc and Neurons With Silenced Wwoxmentioning
confidence: 99%
“…Consistently, neuronal progenitor cells with silenced WWOX showed enhanced adhesion to extracellular matrix proteins, downregulation of MMP2/9 expression, and impaired 3D growth. 48 Recently, it has been reported that WWOX knock out in mice indeed cause a disruption of neuronal migration in developing cerebral cortex, hippocampus, and cerebellum. Neuronal migration disorders in KO mice result in foliation impairment and brain malformation.…”
Section: Encephalopathymentioning
confidence: 99%